12x+-4+10x+10=

Simple and best practice solution for 12x+-4+10x+10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+-4+10x+10= equation:


Simplifying
12x + -4 + 10x + 10 = 0

Reorder the terms:
-4 + 10 + 12x + 10x = 0

Combine like terms: -4 + 10 = 6
6 + 12x + 10x = 0

Combine like terms: 12x + 10x = 22x
6 + 22x = 0

Solving
6 + 22x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 22x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 22x = 0 + -6
22x = 0 + -6

Combine like terms: 0 + -6 = -6
22x = -6

Divide each side by '22'.
x = -0.2727272727

Simplifying
x = -0.2727272727

See similar equations:

| -15-c=4c | | y+5=4 | | -2x^2+5x+21=0 | | 11c+2=6c+12 | | 123456789x+987654321y=1234569 | | 6h=6y | | 4(1-m)=6 | | 2h=134+8h-362 | | -10x+17=23 | | 17w-9w=6w-20 | | 2(y+6)=12 | | -0.6x=15 | | 57.99+0.11h=58.54 | | -4x+7=-(1+8x)-4(-x+1) | | 7x-5y=20 | | 23=9-2x | | 3x^2=4x+15 | | -30=6(-15) | | (2x-4)-[(x+2)(x-4)]=x^2-4 | | 8x+6(1x+5)=15x-6 | | 100y+60x=320 | | -2x-11x-104=130 | | 45x+23x=1023 | | x+109+x+89= | | -34=x-17 | | 6x+5x+10= | | 8x-2=8(x+7) | | t^2-81u^2=0 | | (r+9)/4=3.5 | | -(x-3)=x+3 | | 4.2(10x)=4 | | -5+6k=1+7k |

Equations solver categories